Media Daring dan Kuantitas Pemberian Tugas Terhadap Kepuasan Belajar Mahasiswa - Juhji Juhji; Moch Syamsuri Rachman; Nurjaya Nurjaya (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2020)
The research aims to analyze the influence of online media and the number of lecture assignments on the learning satisfaction of Islamic Education students. The research method uses ex-post facto, conducted on 138 Islamic Religious Education students in the academic year 2019/2020. The data is retrieved through a Google Form that is distributed to all students. Validity and reliability tests are carried out on research instruments. Normality and Homogeneity testing is performed as a prerequisite for further tests. The data is analyzed through the help of SPSS 16.0. The results showed that the number of assignments and online media simultaneously proved not to affect student learning satisfaction. Other factors affect student learning satisfaction. This research recommends that further research be conducted related to student learning satisfaction.